2012
DOI: 10.1124/dmd.112.046086
|View full text |Cite
|
Sign up to set email alerts
|

Human UDP-Glucuronosyltransferase Expression in Insect Cells: Ratio of Active to Inactive Recombinant Proteins and the Effects of a C-Terminal His-Tag on Glucuronidation Kinetics

Abstract: ABSTRACT:Many laboratories use recombinant UDP-glucuronosyltransferases (UGTs), expressed in baculovirus-infected insect cells, for drug glucuronidation studies. We have infected Sf9 insect cells with increasing amounts of recombinant baculovirus, encoding either UGT1A9 or UGT2B7, and measured both glucuronidation activity and immunodetectable UGT in the resulting cell homogenates. The correlation between glucuronidation rates and degree of infection followed different trends, depending on whether activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Briefly, the zebrafish Ugt open reading frame from each of the 40 pGEM-T plasmids (Huang and Wu, 2010) was subcloned with primers (Supplemental Table 2) into the expression vector pcDNA3 containing a myc tag and confirmed by sequencing. It has been shown that the C-terminal tag does not interfere with the glucuronidating activity of the recombinant human UGT protein (Zhang et al, 2012). For recombinant zebrafish UGT production, human embryonic kidney (HEK)293T cells were transfected at 90% confluency in a 10-cm dish with 12 mg of experimental or mock plasmids using Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the zebrafish Ugt open reading frame from each of the 40 pGEM-T plasmids (Huang and Wu, 2010) was subcloned with primers (Supplemental Table 2) into the expression vector pcDNA3 containing a myc tag and confirmed by sequencing. It has been shown that the C-terminal tag does not interfere with the glucuronidating activity of the recombinant human UGT protein (Zhang et al, 2012). For recombinant zebrafish UGT production, human embryonic kidney (HEK)293T cells were transfected at 90% confluency in a 10-cm dish with 12 mg of experimental or mock plasmids using Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…The different recombinant His-tagged dog UGTs were produced in sf9 insect cells, and cell homogenates were used as the study material in the activity assays. Total protein concentrations and relative expression levels of each recombinant dUGT were determined as described previously elsewhere (Zhang et al, 2012a).…”
Section: Methodsmentioning
confidence: 99%
“…30.6% coefficient of variation for rUGT1A4), which may hinder IVIVE-based prediction of both hepatic and renal glucuronidation clearance (14). In addition, UGTs expressed in insect cells may have a substantial amount of inactive protein present that can be reduced by lowering the amount of baculovirus used to infect cells (21). Therefore, the use of metabolic rate data from recombinant UGTs in a quantitative IVIVE setting may require correction for presence of inactive enzyme.…”
Section: Use Of In Vitro Systems To Understand Renal Drug Eliminationmentioning
confidence: 99%